Record Stability for Fully Passive Perovskite‐Based X‐Ray Detectors Through the Use of Starch as Templating Agent - Matteo Verdi; Antonella Giuri; Andrea Ciavatti; Aurora Rizzo; Carola Esposito Corcione; Laura Basiricò; Silvia Colella; Beatrice Fraboni (Advanced Materials Interfaces, 2023)
Abstract High sensitivity and efficient X‐ray detectors are needed to promote and boost their application as tools in medical diagnostics and radiotherapy. Lead halide perovskites have emerged recently as a novel class of material for efficient X‐ray detection. Although 3D perovskites possess very interesting optoelectronic properties they suffer from low environmental and operational stability. Here a strategy based on using starch as a polymeric template for the fabrication of stable thin film perovskite X‐ray detectors is reported. The proposed p‐i‐n photodiodes can operate with no external bias applied (fully passive devices), reaching a top sensitivity of 5.5 ± 0.2 µC Gy−1 s−1. The device degradation is monitored for samples stored in air for a time window of 630 days, demonstrating exceptional stability: 97% of the initial sensitivity is retained for the best perovskite‐starch composite formulation making it the most stable unencapsulated perovskite X‐ray detector reported so far.